Integration of Smart Building Technology in Green Building Concept to Improve Energy Efficiency - Apriyanto, Apriyanto; Hidayat, Deddy (West Science Information System and Technology, 2025)
The integration of smart building technology within green building concepts offers a promising approach to enhancing energy efficiency. This qualitative study investigates the perspectives of five industry experts, including architects, engineers, and smart technology developers, on the challenges, opportunities, and best practices for combining these two approaches. Findings reveal that smart technologies, such as IoT-enabled sensors, adaptive systems, and real-time monitoring, significantly enhance energy optimization in green buildings. However, challenges such as high initial costs, interoperability issues, and limited user awareness persist. The study highlights the need for interdisciplinary collaboration, regulatory incentives, and user-centric solutions to ensure successful implementation. These insights contribute to a deeper understanding of the synergies between smart and green technologies, emphasizing their potential to transform sustainable building practices.